The Influence of College Sports Services on Sports Behavioral Intentions: A Mediation Model Based on Satisfaction and Involvement. (16th August 2022) - Zhou, Zixiang; Yu, Ronghui; Cui, Hao; Chen, Yinggang; Li, Yixiang
Abstract : To learn more about the impact of college sports services on student sports activity intentions, as well as the function of pleasure and involvement as a mediating factor in this process. According to the nature of the service, this study separates college sports services into basic and advanced sports two types, selects 482 students from five institutions in Hunan Province for a questionnaire survey based on spatial dimensions, and analyzes the data using a structural equation model. The findings show that (1) there is a positive correlation between college students' perception levels of basic and advanced sports services ( p = 0.01); (2) perception of basic sports services is closely related to cognize involvement ( r = 0.717), and perception of advanced sports services is closely related to affective involvement ( r = 0.830); and (3) perception of basic sports services is closely related to cognize involvement ( r = 0.717). (3) Satisfaction and involvement show a substantial mediation effect between sports service and sports behavioral intention, with involvement having a bigger influence on sports behavioral intention (effect percent = 52.63%) than satisfaction. (4) Advanced sports services are easier to improve students' behavioral intentions than basic sports services in a comparison of the two categories of college sports services. To summarize the findings of the four studies, it can be seen that ensuring the balanced development of basic and advanced sports services, adjusting service content to increase student involvement, and improving resource allocation to advanced sports service content are all effective ways to strengthen students' sports behavioral intention in the service strategy.